HEBREW GRAMMATICAL EXPRESSION AND ANALYSIS OF PSALM 1:1-3 - Gosal, Fellix (Klabat Theological Review; Vol 4 No 2 (2024): Klabat Theological ReviewDO - 10.31154/ktr.v4i2.1203.112-145, 2024)
This article presents a thorough morphological examination of Psalm 1:1-3, focusing on the grammatical terms used in Hebrew in these passages. The study employs word analysis methodology, investigating the root, affixes, verb forms, and particle usage of each term. Through close examination of the text, the study unveils subtleties of meaning that add to the psalm’s overall meaning and literary mastery. The study illustrates the depth of Biblical Hebrew morphology and shows how this morphological method improves our comprehension of the psalm’s meaning. The word comprises a sentence analysis based on Hebrew accent marks as well as a pericope analysis that splits the material into three portions. This thorough analysis provides insights into the blessings of the righteous as they are described in Psalm 1:1-3, leading to a translation that reflects a depth of the Hebrew linguistic structures. Keyword: Biblical Hebrew, Psalm 1, morphological analysis, pericope analysis, syntactical analysis, Hebrew grammar, biblical poetry, exegesis, Torah.